Solid Polymer Electrolytes with High Conductivity and Transference Number of Li Ions for Li‐Based Rechargeable Batteries. Issue 7 (8th February 2021) - Zhao, Yun; Wang, Li; Zhou, Yunan; Liang, Zheng; Tavajohi, Naser; Li, Baohua; Li, Tao
Abstract: Smart electronics and wearable devices require batteries with increased energy density, enhanced safety, and improved mechanical flexibility. However, current state‐of‐the‐art Li‐based rechargeable batteries (LBRBs) use highly reactive and flowable liquid electrolytes, severely limiting their ability to meet the above requirements. Therefore, solid polymer electrolytes (SPEs) are introduced to tackle the issues of liquid electrolytes. Nevertheless, due to their low Li + conductivity and Li + transference number (LITN) (around 10 −5 S cm −1 and 0.5, respectively), SPE‐based room temperature LBRBs are still in their early stages of development. This paper reviews the principles of Li + conduction inside SPEs and the corresponding strategies to improve the Li + conductivity and LITN of SPEs. Some representative applications of SPEs in high‐energy density, safe, and flexible LBRBs are then introduced and prospected. Abstract : Recent advancements in solid polymer electrolytes (SPEs) for Li‐based rechargeable batteries are summarized. The principles of Li‐ion conduction inside SPE and the corresponding strategies to improve Li‐ion conductivity and transference number are first reviewed. The representative applications of SPEs in high‐energy density, safe, and flexible batteries are then introduced and prospected.